This is what inequality looks like essays - Teo, You Yenn (Strategic Information and Research Development Centre, 2019)
This book-an ethnography of inequality- addresses these qu estions. Formed by a series of essays, th ey are written to be read individually, but have been arrange d to be read as a tot alit y and in sequence. Each aims to accomplish two things: first, to introduce a key aspect of the expe rience of being low-income in contempo ra ry Singapore. Second, to illustr ate how people's expe riences are linked to structural conditions of inequality. The way we frame our qu estions shapes th e way we see solutions. This book does what appears to be a no-brainer task, but one that is missing and import ant: it asks readers to pose qu estion s in different ways, to shift th e vantage point from which they view 'common sense,' and in so doing, to see themselves as part ofproblem s and potenti al solutions. T his is a book about how seeing poverty entails confronting inequality. It is about how acknowledging poverty and inequalit y leads to uncomfortable revelations about our society and ourselves. And it is about how once we see, we cannot, must no t, unsee.